2015
DOI: 10.1093/hmg/ddv240
|View full text |Cite
|
Sign up to set email alerts
|

POLG2disease variants: analyses reveal a dominant negative heterodimer, altered mitochondrial localization and impaired respiratory capacity

Abstract: Human mitochondrial DNA (mtDNA) is replicated and repaired by the mtDNA polymerase gamma, polγ. Polγ is composed of three subunits encoded by two nuclear genes: (1) POLG codes for the 140-kilodalton (kDa) catalytic subunit, p140 and (2) POLG2 encodes the ∼110-kDa homodimeric accessory subunit, p55. Specific mutations are associated with POLG- or POLG2-related disorders. During DNA replication the p55 accessory subunit binds to p140 and increases processivity by preventing polγ's dissociation from the template.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…The p140 catalytic subunit harbors active sites for 5′-3′ DNA polymerase, 3′-5′ exonuclease, and 5′ dRP lyase activities [9,10]. The p55 imparts high processivity onto the holoenzyme by increasing the binding affinity to DNA [4,11]. The majority of intermolecular contacts occur between the C-terminal region of the ‘proximal’ p55 monomer (purple in Figure 2) and the AID subdomain (Accessory-Interacting Determinant subdomain that extends an an ‘arm’ around p55) of the p140 catalytic subunit [1215].…”
Section: The Mtdna Replisomementioning
confidence: 99%
See 2 more Smart Citations
“…The p140 catalytic subunit harbors active sites for 5′-3′ DNA polymerase, 3′-5′ exonuclease, and 5′ dRP lyase activities [9,10]. The p55 imparts high processivity onto the holoenzyme by increasing the binding affinity to DNA [4,11]. The majority of intermolecular contacts occur between the C-terminal region of the ‘proximal’ p55 monomer (purple in Figure 2) and the AID subdomain (Accessory-Interacting Determinant subdomain that extends an an ‘arm’ around p55) of the p140 catalytic subunit [1215].…”
Section: The Mtdna Replisomementioning
confidence: 99%
“…Because currently identified POLG2 patients harbor heterozygous mutations, and because monomers within the p55 homodimer do not readily dissociate, the patients should harbor a mixture of p55 molecules: 25% WT homodimers, 25% variant homodimers, and 50% heterodimers [4]. Using a tandem affinity strategy and biochemistry to study p55 heterodimers we showed that one p55 disease variant, G451E, is dominant negative and associates with a wild-type p55 monomer in pol γ to poison the enzyme’s activity.…”
Section: Disorders Of Polg2 the Mtdna Polymerase γ P55 Processivity mentioning
confidence: 99%
See 1 more Smart Citation
“…POLG2 encodes the accessory subunit of DNA polymerase γ, and is required for imparting high processivity to POLG by increasing the affinity of the protein complex to DNA [Lim and others 1999]. Biochemical and functional studies of one pathogenic missense mutation (c.1352G>A; p.G451E) showed decreased processivity of the enzyme complex leading to multiple mitochondrial DNA deletions [Young and others 2015; Young and others 2011]. The second reported heterozygous insertion (c.1207–1208ins24) mutation causes mis-splicing and skipping of exon 7, thereby impairing the C-terminal domain that is required for processivity [Walter and others 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in POLG2 that cause disease have been shown to be defective in their ability to bind the catalytic subunit, bind to double stranded DNA, and/or self-dimerize (Craig et al 2012; Longley et al 2006; Young et al 2011). Cell and biochemical studies by Young et al showed that mutant POLG2 heterodimers can either poison the enzyme activity of the mtDNA polymerase or fail to bind nucleoids, ultimately leading to failed mtDNA replication, decreased bioenergetics and contributes to mitochondrial disease seen in patients (Young et al 2015). The TWNK mtDNA helicase, also known as Twinkle, is essential for mtDNA replication as it is needed to unwind the double helix ahead of the replication fork, as well as synthesis of nascent D-loop strands (Milenkovic et al 2013).…”
Section: Origins and Consequences Of Mtdna Instabilitymentioning
confidence: 99%